Stimulant abuse as a coping strategy—Forensic and criminal consequences of stimulant abuse for neuroenhancement - Dominik, Philipp; Waßmer, Martin P.; Soyka, Michael; Franke, Andreas G. (Frontiers in Public Health, 2022)
Pharmacological neuroenhancement (PN) describes the use of divergent psychoactive substances to enhance mental performance (cognition) without medical need. This kind of substance abuse takes place predominantly in stressful situations. Users implicitly – or even explicitly – describe this kind of drug abuse to be a coping strategy. Regarding the decision making process whether to use PN drugs or not, users indicate that legal aspects to be decisive. However, the legal situation has been neglected so far. To elucidate the German legal situation, PN substances have to be divided into over-the-counter drugs, prescription drugs and illegal drugs. Amphetamines have the highest cognition-enhancing potential, followed by modafinil and caffeine-containing substances. It is pointed out that the use of both freely available and prescription PN substances and narcotics without medical indication have so far been largely exempt from punishment under German law. However, individuals (physicians, bus and truck drivers, etc.) taking PN substances may expose others at risk due to wrong decisions, (driving or treatment) errors based on side effects of the used substances. Therefore, the protection of life and health of others could legitimise criminal regulation.